The winter habits of plants - Bergman, Herbert F. (My University, 1905)
Introduction: In climates there is a period at some time of the year when plants cannot continue to live in an active state, but are required, by environmental conditions, to assume a form that will enable them to live through the unfavorable period. Whether a plant must pass through a period of cold, unfavorable to plant activity, or through a periodic drouth, the methods of meeting both these adverse conditions are the same. Since, in the temperate zone, it is the cold against which the plants must protect themselves, the forms assumed by them for protection during the winter are called their winter habits. If one should take a stroll through the fields or woods in the fall, he would notice that all plants do not succumb to the cold at the same time. Some plants cease activity at the "first suggestion of cold, while others continue through a. long succession of frosts before they perish. For example, such trees as the Maple, Boxelder, and Ash shed their leaves early, while cottonwood, elms and oaks cone somewhat later; many oaks retaining their leaves throughout the winter, shedding them early the following spring. Other plants yet, such as conifers, mosses, liver-orts and lichens, live through the winter with no apparent change. Between the group of plants which are killed by the winter, and the group which survive without apparent change in outward forms, stand the deciduous plants which cast their leaves and the herbaceous plants with thickened underground stems or roots wherein the living substance, withdrawn from the leaves and stems, is able to survive the winter. The degree of cold necessary to cruse the death of any plant depends upon the nature of the protoplasm, i, e. the ability of the protoplasts of that kind of plant to withstand adverse conditions, and also upon the stage of development or activity of the plant at the time it is subjected to the cold.
Citation: Bergman, Herbert F. The winter habits of plants. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Helianthus tuberosa; Rhizome; Rootstack; Theses